The Effect of Water Limitation on Volatile Emission, Tree Defense Response, and Brood Success of Dendroctonus ponderosae in Two Pine Hosts, Lodgepole, and Jack Pine - Lusebrink, Inka; Erbilgin, Nadir; Evenden, Maya L. (Frontiers in Ecology and Evolution, 2016)
The mountain pine beetle (MPB; Dendroctonus ponderosae) has recently expanded its range from lodgepole pine forest into the lodgepole × jack pine hybrid zone in central Alberta, within which it has attacked pure jack pine. This study tested the effects of water limitation on tree defense response of mature lodgepole and jack pine (Pinus contorta and Pinus banksiana) trees in the field. Tree defense response was initiated by inoculation of trees with the MPB-associated fungus Grosmannia clavigera and measured through monoterpene emission from tree boles and concentration of defensive compounds in phloem, needles, and necrotic tissues. Lodgepole pine generally emitted higher amounts of monoterpenes than jack pine; particularly from fungal-inoculated trees. Compared to non-inoculated trees, fungal inoculation increased monoterpene emission in both species, whereas water treatment had no effect on monoterpene emission. The phloem of both pine species contains (-)-α-pinene, the precursor of the beetle’s aggregation pheromone, however lodgepole pine contains two times as much as jack pine. The concentration of defensive compounds was 70-fold greater in the lesion tissue in jack pine, but only 10-fold in lodgepole pine compared to healthy phloem tissue in each species, respectively. Water-deficit treatment inhibited an increase of L-limonene as response to fungal inoculation in lodgepole pine phloem. The amount of myrcene in jack pine phloem was higher in water-deficit trees compared to ambient trees. Beetles reared in jack pine were not affected by either water or biological treatment, whereas beetles reared in lodgepole pine benefited from fungal inoculation by producing larger and heavier female offspring. Female beetles that emerged from jack pine bolts contained more fat than those that emerged from lodgepole pine, even though lodgepole pine phloem had a higher nitrogen content than jack pine phloem. These results suggest that jack pine chemistry is suitable for MPB pheromone production and aggregation on the host tree.